PENGARUH KOMUNIKASI INTERPERSONAL PEDAGANG DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI TOKO HANG TUAH PASAR FANINDO BATAM - Renaldi Faslah Faslah; Michael Jibrael Rorong (LPPM Universitas Putera Batam, 2026)
This study aims to examine the effect of traders’ interpersonal communication and service quality on customer satisfaction at Hang Tuah Store, Pasar Fanindo Batam. This research employs a quantitative approach using a correlational method. Data were collected through questionnaires distributed to 96 customers of Hang Tuah Store using a Likert scale. The variables in this study consist of interpersonal communication and service quality as independent variables, and customer satisfaction as the dependent variable. Data analysis techniques include descriptive statistics, validity and reliability tests, classical assumption tests, Pearson Product Moment correlation analysis, simple and multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing using t-tests and F-tests, assisted by SPSS version 25. The results indicate that traders’ interpersonal communication has a significant effect on customer satisfaction. Service quality also has a significant effect and is identified as the most dominant factor influencing customer satisfaction. Simultaneously, interpersonal communication and service quality significantly affect customer satisfaction at Hang Tuah Store, Pasar Fanindo Batam. These findings support the Expectancy Disconfirmation Theory (EDT), which states that customer satisfaction is formed through a comparison between expectations and perceived performance.